Evaluating luteinizing hormone receptor function using the cyclic AMP reporter probe ICUE1 - Shnaishah, Hoda Ramadhan, author; Roess, Deborah, advisor; Barisas, B. George, committee member; Miller, Charles W., committee member (Colorado State University. Libraries, 2011)
Luteinizing hormone receptors (LHR) are G protein-coupled membrane protein receptors. Mechanisms involved in initiation of signal transduction by luteinizing hormone (LH) receptors are important and they have been under active investigation because they play a vital role in regulating key events in mammalian reproduction. Evaluating cAMP levels in response to hormone treatment is usually used to demonstrate LH receptor activation and has historically relied on biochemical methods. ELISA, colorimetric assays and other techniques have been used to evaluate cAMP levels. ICUE1 is an Epac-based cAMP reporter which undergoes conformational changes upon binding cAMP. Unlike traditional biochemical assays, ICUE1 combined with FRET techniques is capable of real-time monitoring of cAMP levels in individual cells. In this project, Epac reporters have been used to evaluate LH receptor activity in cells expressing ICUE1 only and in cells expressing ICUE1 and constitutively-active LH receptors. For the investigation of constitutively active LH receptors, CHO cells were co-transfected with DNA of ICUE1 and yoked LH receptor and they were expressed on the cell membrane. Our results show that ICUE1 probe is a useful tool for evaluating cAMP levels in real-time using single cell imaging methods. Hormone treatment of CHO cells expressing constitutively active LH receptors show that cAMP levels measurable increase than the basal level in the cell. Similarly, treatment of these cells with forskolin cusese an increase in cAMP levels due to the increase in adenylate cyclase activity.